Analisis Kinerja Ground Handling Guna Meningkatkan Keselamatan Area Sisi Udara di Bandar Udara International Yogyakarta - Ozwaldo Henriquez; Sundoro Sundoro; Yenni Arnas (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to improve ground handling personnel to support operational safety in the airside area of Yogyakarta International Airport. The main focus of this study is the level of compliance with the technical provisions stipulated in SKEP 140/VI/1999. The approach used is descriptive qualitative, with data collected through direct field observation, interviews with competent parties, and review of related documents. The results of the study indicate that there are still many violations of standard operating procedures (SOPs), especially related to the use and placement of Ground Support Equipment (GSE) that does not comply with standards and the operation of vehicles that do not reach properly. Some of the main causes identified are weak supervision, low work discipline, limited understanding of safety procedures, and a lack of routine training for officers. This has the potential to increase safety risks and disrupt smooth operations at the airport. As a solution, this study recommends corrective measures that include strengthening field supervision, ongoing training to improve understanding of safety procedures, implementing strict sanctions for violators, and reorganizing equipment storage and use areas. In addition, it is important to develop a stronger safety culture among officers and utilize technology to improve operational oversight. These measures are expected to create a safer and more efficient environment in the airside area of Yogyakarta International Airport. This study also identified the need for regular evaluation and updating of existing procedures to align with technological developments and international standards. By paying attention to safety aspects, operational efficiency can be maintained and the risk of accidents or incidents can be minimized. By strengthening safety management and work discipline, better performance levels and improved service quality in the aviation sector can be achieved.